Development of small business and private entrepreneurship with the help of investments - Abdiyeva, Nilufar (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
The article examines the role of investments in the country's economy and their impact on the development of small businesses and private entrepreneurship.